The Effect of Differentiated Learning Through Gross Motor Skills on Physical Fitness in Physical Education Learning - Finny Rohaeni Finny; Indra Safari; Dinar Dinangsit (UNIB Press, 2024)
This research aims to determine the effect of differentiated learning through gross motor skills on physical fitness in physical education learning. The method used is quasi-experimental. The population of this research is class IV students at SDN 254 ​​Griya Bumi Antapani Bandung for the 2023/2024 academic year, totaling 54 people. The sample used was 26 people. The instrument used is TKSI Phase B with 5 test items, that’s: V Sit and Reach Test, Half Up Test, Hand Eye coordination Test, T Test, and Around the World Test. The data analysis techniques used are Paired Sample T-Test, and Linear Regression using the SPSS For Windows 20 application, at the Sig T Test level. (0.000) < 0.05. Based on the results of data analysis, this research shows that there is an influence of differentiated learning through gross motor skills on physical fitness in physical education learning. Also supported by the results of data analysis carried out using the R Square test, the results showed that the magnitude of the effect between the pre-test and post-test experimental data was 0.111% x 100%. In this way, the increase in the influence of learning with differentiated programs through gross motor skills on physical fitness in physical education is 11.1%. So with the results of data analysis, it can be concluded that there is an influence of differentiated learning through gross motor skills on physical fitness in physical education learning, and differentiated learning has an effect on improving gross motor skills on the physical fitness of class IV students at SDN 254 ​​Griya Bumi Antapani Bandung.